The origin and evolution of investment treaty standards : stability, value, and reasonableness - Ortino, Federico (Oxford : Oxford University Press, 2020)
This title provides a conceptual and legal analysis of the core of investment protection guarantees that emerge from international treaties signed since 1959 for the promotion and protection of foreign investment. It focuses on both the origin and evolution of investment treaty standards. Beginning with origins, the work considers the broader context at the time when the first modern investment treaty was concluded. It goes on to examine the many decisions of ad hoc arbitral tribunals that have since been called upon to apply these treaties in order to resolve the several hundred investor-State disputes. It also looks at some of the recent investment treaties that have attempted to clarify and/or reform the content and scope of investment protection guarantees.
This edition previously issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 14, 2020).
Keywords: Investments, Foreign (International law); Law; Laws of specific jurisdictions & specific areas of law